Pharmacokinetics of Morphine, Morphine-3-Glucuronide and Morphine-6-Glucuronide in Terminally Ill Adult Patients - Franken, Linda G. (Clin Pharmacokinet, 2015)
BACKGROUND AND OBJECTIVE: Morphine dosing can be challenging in terminally ill adult patients due to the heterogeneous nature of the population and the difficulty of accurately assessing pain during sedation. To determine the pharmacokinetics of morphine, morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G) in this population, and to find clinically relevant parameters for dose individualisation, we performed a population pharmacokinetic analysis. METHODS: Blood samples were randomly collected from 47 terminally ill patients in both the pre-terminal and terminal phases. Nonlinear mixed-effects modelling (NONMEM) was used to develop a population pharmacokinetic model and perform covariate analysis. RESULTS: The data were accurately described by a two-compartment model for morphine with two one-compartment models for both its metabolites. Typical morphine clearance was 48 L/h and fell exponentially by more than 10 L/h in the last week before death. Decreased albumin levels and a decreased estimated glomerular filtration rate (eGFR) resulted in lower metabolite clearance. Between-subject variability in clearance was 52 % (morphine), 75 % (M3G) and 79 % (M6G), and changed to 53, 29 and 34 %, respectively, after inclusion of the covariates. CONCLUSIONS: Our results show that morphine clearance decreased up to the time of death, falling by more than 10 L/h (26 %) in the last week before death, and that M3G and M6G accumulated due to decreased renal function. Further studies are warranted to determine whether dose adjustment of morphine is required in terminally ill patients.